2015
DOI: 10.1111/jcpt.12265
|View full text |Cite
|
Sign up to set email alerts
|

Subtherapeutic serum quetiapine concentrations after absorption inhibition by binding resins: a case report

Abstract: Polystyrene sulfonate and sevelamer are able to bind quetiapine. Healthcare professionals should be aware of this potential drug-drug interaction as this could lead to antipsychotic treatment failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…In vitro experiments, to assess binding to resins, have been described in literature before. 21 , 23 , 32 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 The sensitivity of in vitro studies for identifying compounds binding to resins is high, but the specificity may be low. 32 Studies confirming that in vitro binding is also clinically relevant in vivo have been described for different drug–resin combinations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In vitro experiments, to assess binding to resins, have been described in literature before. 21 , 23 , 32 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 The sensitivity of in vitro studies for identifying compounds binding to resins is high, but the specificity may be low. 32 Studies confirming that in vitro binding is also clinically relevant in vivo have been described for different drug–resin combinations.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Studies confirming that in vitro binding is also clinically relevant in vivo have been described for different drug–resin combinations. 21 , 22 , 32 , 39 , 40 , 42 , 43 However, there are also several studies in which in vitro binding could not be confirmed in vivo to the same extent. 32 , 34 , 36 , 41 , 44 , 45 , 46 This can be explained by the fact that drug absorption from the gastrointestinal tract is affected by many different factors such as absorptive surface area, pH, food effects, co‐medication, intestinal transit time, passive intestinal permeability, intestinal transporters, and enzymes that are not accounted for in vitro .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations